Agroforestri Lahan Gambut Tanpa Bakar - Fahruni Fahruni (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2019)
Peatland agroforestry management that is commonly carried out by the community is the burnt peel system. Where peat is peeled and burned, it is then used as a planting medium. Over time, this system will reduce the land surface. But there is a different system. Through the method without combustion by adding organic material above the soil surface. So as the land surface does not decrease, it will even increase in height. This study aims to (1) determine the ecological value of land with a peel-burn system and the addition of minerals without fuel, (2) determine the effectiveness of the peatland management system. The variables observed / measured in this study were (1) the content of macro nutrients (N, P, K) from the system pattern of management of firewood peel and the management system of mineral soil addition. (2) Agroforestry patterns implemented by farmers at the study site. The results showed that the method of agroforestry without burning provides more nutrients than peeled fuel. Increased soil pH is also higher than burnt peel. This method is more environmentally friendly because the peat ecosystem is maintained and the most important thing is the height of the land surface continues to increase during the exploitation time.